The notion of Threshold: an investigation into conceptual accompaniment in Aristotle and Hegel - Jason Carter (Conserveries Mémorielles)
What is unique to the idea of a threshold is that it is a threshold’s proper definition to generate or signal an inevitable accompanying image of a surrounding boundary or a further field of exploration, even though these accompanying terms or images seem like they should be excluded from its definition. Hegel described this phenomenon of the movement from a concept’s definition to its accompanying terms as the determination of a concept through ‘negation’, and viewed such a method as central to philosophical insight. However, what is not usually noted is that Hegel’s notion of negation is both crucially related to Aristotle’s thought on how definitions are formulated, as well as his postulations about opposites and their connection through a third substantial thing. Through a close examination of the problem of Aristotle’s categories, along with Aristotle’s description of the differentiae, movement, and the meaning of the copula, we can demonstrate that Aristotle’s thinking is at core structured by non-binary ‘threshold concepts’ which are essential to his philosophical system. Finally, we will show how Hegel attempted to take these essentially structural threshold concepts in Aristotle and turn their function into a methodology for both thought itself as well as the philosophical determination of the categories of being.